THE ROLE OF CAPITAL STRUCTURE IN ENHANCING CORPORATE - Bakoeva Gulbakhor, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Annotation: The purpose of this paper is to explore how a firm’s capital structure can influence and enhance its financial stability. The study first reviews the major theoretical perspectives on capital structure — including the trade-off theory, pecking order theory, and the Modigliani-Miller framework — and then examines empirical evidence linking capital structure decisions to corporate financial stability. It is argued that an optimal balance between debt and equity financing is crucial not only for performance but also for the resilience of firms during adverse economic conditions. The paper highlights how high leverage may increase risk of financial distress, whereas prudent financing decisions enhance stability and sustainability. Key implications for corporate finance managers and policymakers are drawn.